The users’ perception on the planning of intermodal freight transport terminal in Peninsular Malaysia / Mohd Sabri Mohd Arip - Mohd Arip, Mohd Sabri (2014)
There is the need to consider the establishment of strategic logistic centers such as a comprehensive intermodal freight transport terminal to support the tremendous pace of logistics development in Malaysia. There are some problems of transportation and goods distribution in this country such as documentation, custom clearance process, terminal locations, planning issues and transportation as well as distribution using service trucks. These are the consequences from having lack of sophisticated mechanism development of intermodal freight transport terminals in Malaysia. This has become a major challenge to the industry which must be overcome immediately. The existence of ports, inland ports and distriparks play an important role as a mechanism with infrastructures and operational systems such as an intermodal freight transport terminal which have been developed in several countries such as the United States as well as some parts in Europe and Asia. On that reason, the scope of study focuses on Peninsular Malaysia as a major research area where ports, inland ports and distriparks are fundamental by looking at the efforts of these terminals in handling transportation and goods distribution activities. This study focuses on three important elements in planning comprehensive ports, inland ports and distriparks in Malaysia namely; the physical elements, core-on site service elements and core-on site activity elements to enhance goods transportation and distribution system performance for these terminals. A survey was conducted by the researcher towards 257 freight forwarder companies and several discussions with public and private sectors in completing this study. The data was analysed using statistical and multiple regression analysis in order to improve the terminal and to measure the performance of the terminals studied. The main findings from the analysis showed that the terminals need improvement to increase transportation and distribution system performance. Findings also show that goods distribution system have a very high level of significance with the three intermodal freight transport terminal elements namely; physical elements, core-on site service elements and core-on site activity elements at ports, inland ports and distriparks in Peninsular Malaysia. Recommendations on guidelines and planning standards were developed to enhance terminal capabilities for the goal of constructing a comprehensive intermodal freight transport terminal.